Kenya Broadcasting Corporation (2017)
KerkoCite.ItemAlsoKnownAs: 2405685:RYQDKX8X

EdTech East Africa (Edtech Meetup, 2017)
Library Catalog: edtecheastafrica.com EdTechHub.ItemAlsoKnownAs: 2405685:GN64Y5CP

International Telecommunications Union (2017)
KerkoCite.ItemAlsoKnownAs: 2405685:49IVAHYE

Effects of Information and Communication Technology (ICT) on Students' Academic Achievement and Retention in Chemistry at Secondary Level - Hussain, Ishtiaq; Suleman, Qaiser; ud Din, M. Naseer; Shafique, Farhan (Journal of Education and Educational Development, 2017)
The current paper investigated the effects of information and communication technology on the students' academic achievement and retention in chemistry. Fifty students of 9th grade were selected randomly from Kohsar Public School and College Latamber Karak. The students were grouped into equivalent groups based on pretest score. In order to collect data, pretest posttest equivalent groups design was used. Mean, standard deviation and independent samples t-test were applied through SPSS for data analysis. Based on statistical analysis, it came to light that information and communication technology positively affects students' academic achievement and retention and ICT was found more compelling, effective and valuable in teaching of chemistry when contrasted with conventional techniques of teaching. It is recommended that information and communication technology should be used in teaching chemistry for enhancing students' academic achievement at secondary level.
Publisher: Institute of Business Management, Department of Education KerkoCite.ItemAlsoKnownAs: 10.22555/joeed.v4i1.1058 2339240:PEKV6S35 2405685:DKAAC8HF
Keywords: Chemistry; Computer Uses in Education; Conventional Instruction; Foreign Countries; Influence of Technology; Pretests Posttests; Retention (Psychology); Science Achievement; Science Instruction; Secondary School Science; Secondary School Students; Statistical Analysis

Technology Enters the Classroom: An Evaluation of Educational Technology Initiatives in Punjab - Waqar, Yasira; Bokhari, Tahira Batool (2017)
This article provides a critical review of educational technology initiatives of the Punjab government. The attributes of meaningful learning with technology are used as a criterion to evaluate the benefits of technology initiatives in the education sector. An historical perspective of the integration of technology in Pakistan is given in the beginning to have a clear idea as how technology was introduced in the private schools in 1990s and what are the latest trends in these schools? The initiatives of Punjab government are then elaborated by discussing the following projects: Daanish Schools, School Reform Roadmap, Technology to Improve School Processes and Digitized Textbooks and Intelligent Tutoring System. After an analysis of these initiatives, a review of educational technology initiatives in developing countries is done to compare the successful and not so successful projects of educational technology. The article concludes with suggestions for educationists and policy-makers in Pakistan.
KerkoCite.ItemAlsoKnownAs: 2339240:ZJ2PDNDG 2405685:GESZ38IG

Possible Potential of Facebook to Enhance Learners' Motivation in Mobile Learning Environment - Raza, Mehwish (International Association for the Development of the Information Society, 2017)
Facebook is world's leading social network, 29% of its active members represent Pakistan. This study utilized Facebook for teachers' in-service training. Thirty teachers from different parts of Pakistan took part in this training that lasted for ten weeks. The researcher tested the impact of three independent variables namely: social interactions, quality of experiences and behavior on learners' motivation (dependent variable). The hypothesis of this study propose a positive impact of independent variables on the dependent variable, the research was able to prove the hypothesis. [For the complete proceedings, see ED579190.]
Publication Title: International Association for Development of the Information Society KerkoCite.ItemAlsoKnownAs: 2339240:6KMFB2TP 2405685:5FSFA5SK
Keywords: Educational Technology; Elementary School Teachers; Elementary Schools; Foreign Countries; Handheld Devices; Hypothesis Testing; Interaction; Likert Scales; Pretests Posttests; Private Schools; Questionnaires; Social Media; Statistical Analysis; Student Motivation; Teacher Attitudes; Technology Uses in Education; Telecommunications; Training